Room for a Young Dictator - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet provides instruction for decorating a child's nursery. Describes how young children prefer rooms decorated with primary color schemes, and describes several nurseries for inspiration. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Interior decoration; Paint materials; Nurseries; Nurseries--Decoration; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint